Adaptability and evolution. Issue 5 (6th October 2017) - Bateson, Patrick
Abstract : The capacity of organisms to respond in their own lifetimes to new challenges in their environments probably appeared early in biological evolution. At present few studies have shown how such adaptability could influence the inherited characteristics of an organism's descendants. In part, this has been because organisms have been treated as passive in evolution. Nevertheless, their effects on biological evolution are likely to have been important and, when they occurred, accelerated the pace of evolution. Ways in which this might have happened have been suggested many times since the 1870s. I review these proposals and discuss their relevance to modern thought.